The Clinical and Economic Impact of Exacerbations of Chronic Obstructive Pulmonary Disease: A Cohort of Hospitalized Patients - Blasi, Francesco (Public Library of Science, 2014)
BACKGROUND: Chronic Obstructive Pulmonary Disease (COPD) is a common disease with significant health and economic consequences. This study assesses the burden of COPD in the general population, and the influence of exacerbations (E-COPD) on disease progression and costs. METHODS: This is a secondary data analysis of healthcare administrative databases of the region of Lombardy, in northern Italy. The study included ≥ 40 year-old patients hospitalized for a severe E-COPD (index event) during 2006. Patients were classified in relation to the number and type of E-COPD experienced in a three-year pre-index period. Subjects were followed up until December 31(st), 2009, collecting data on healthcare resource use and vital status. RESULTS: 15857 patients were enrolled –9911 males, mean age: 76 years (SD 10). Over a mean follow-up time of 2.4 years (1.36), 81% of patients had at least one E-COPD with an annual rate of 3.2 exacerbations per person-year and an all-cause mortality of 47%. A history of exacerbation influenced the occurrence of new E-COPD and mortality after discharge for an E-COPD. On average, the healthcare system spent 6725€ per year per person (95%CI 6590–6863). Occurrence and type of exacerbations drove the direct healthcare cost. Less than one quarter of patients presented claims for pulmonary function tests. CONCLUSIONS: COPD imposes a substantial burden on healthcare systems, mainly attributable to the type and occurrence of E-COPD, or in other words, to the exacerbator phenotypes. A more tailored approach to the management of COPD patients is required.